Rapid and simple design approach of micro-strip butler matrix beam-forming network for wireless system - Hock G.C.; Charabarty C.K.; Kiong T.S.; Heong O.K. (Institute of Electronics Information Communication Engineers, 2023)
In this work, a rapid and simple approach is facilitating the design of Butler matrix beam-forming network (BMN). Generally, BMN structure is occupying huge area of printed circuit board and required large amount of mesh cells for better simulation accuracy. The proposed approach has reduced design steps and improves the simulation time. Although, designers can use better mainframe and graphics processing unit in order to improve the simulation time, the devices come with simulation cost. The entire BMN is divided into smaller and simple structure as the standard re-use electromagnetic model in order to study the parasitic elements and essential actual phase progression. IEICE 2012.